REVIEW ABOUT DIABETIC NEPHROPATHY - Sabah kamel neama; Alaa muhannad talib; Jaber Rashid Wannas; saja hadi abad (Journal of Medical Genetics and Clinical Biology, 2024)
The main function of the kidney is to filter the blood, purify it, and then return it to the body. This is done by taking the blood into the kidney through the renal arteries. About one liter of blood is pumped to the kidney, and 1/5 of what the blood pumps is returned. After filtering, the blood returns back to the body through the renal veins diabetes, damage Figure 4: A scan showing the basic structure and function of the kidney: The kidney is associated with to the capillaries, and changes in the afferent and afferent arteries, which interfere with the blood pressure furnace of the capillary and renal blood vessels of many tissues, including the infiltration of the umbilical cord. This can be caused by kidney weakness or kidney failure, and if the kidneys do not function properly for a long period of, When the t and kidney capacity time, this may be the result of diarrhea, diabetes, or high blood pressure. Sometimes this is due to genetic factors, hormones in the body, which help in regulating blood pressure. And the regulates the consumption of calcium in the intestines, and maintains the amount production of red blood cells, in addition to romaine, which of water in the body, which is responsible for the body’s general functions, including blood sugar and controlling the amount of water and salt in the blood and some chemicals (F Walter, 2004). Diabetes Mellitus, Diabetes is known to be a disruption in the process of sugar metabolism, leading to high blood sugar levels (glycolysis).